General Framework for Post-conflict Reconstruction in Yemen - Gaghman, Abdulghani (Technium Social Sciences Journal, 2020)
The war in Yemen, which escalated in March 2015 when a Saudi-led coalition intervened, with comprehensive blockade and air campaign has turned a poor country into a humanitarian catastrophe. The impacts of the conflict in Yemen are devastating—with nearly a quarter of a million people killed directly by fighting and indirectly through lack of access to food, health services, and infrastructure. The economy has collapsed, and fighting has ravaged the country’s infrastructure. The reconstruction and recovery of Yemen will demand rebuilding the economy, restoring state institutions and infrastructure and repairing the social fabric. Good governance plays a key role in rebuilding Yemen as a post-conflict state. The task is thus to build transparent, efficient and participative governance structures that can help to stabilise the volatile transformation of post-conflict society. This paper intends to clarify how good governance can be promoted in Yemen as conflict / post-conflict country and which role the political and administrative system could play in this context. This paper is based on a literature review of the main theories and issues involved in post-conflict reconstruction, coupled with an analysis of relevant case studies and good practices from different countries. The main recommendations most urgently needed are; establishing safety and security, strengthening constitutional government, reconstructing infrastructure and restoring services, stabilizing and growing the economy, and strengthening justice and reconciliation organizations.